Uji Keamanan Back End Aplikasi Berbasis Website Menggunakan Metode Black Box Testing - Abd. Wahab Syahroni; Nindian Puspa Dewi; Nilam Ramadhani; Ubaidi; Badar Said (Jurnal PROCESSOR, 2024)
Application security is often overlooked during the development phase and even after the application is deployed. However, without proper security measures, even the most advanced technologies can lead to significant losses, such as unauthorized data access and potential data loss due to deletion actions. Developing applications using the REST API architecture allows users to access backend endpoints from outside the application, so attention must be given not only to authentication but also to authorization issues. Based on the results of testing the SILAB application using the Black Box Testing method, it can be concluded that the SILAB application still needs improvements in backend security, particularly in terms of authorization. This indicates that there are still vulnerabilities and threats that could potentially compromise the data in the SILAB application.